Development of a low cost and green microwave assisted approach towards the circular carbon fibre composites. (1st March 2020) - Zabihi, Omid; Ahmadi, Mojtaba; Liu, Chao; Mahmoodi, Roya; Li, Quanxiang; Naebe, Minoo
Abstract: In this study, we have developed a rapid, cost-effective, environmentally green, and yet efficient approach for the complete reclamation of the carbon fibre composites through a microwave assisted chemical method. It was found that in a catalyst-free and one-step process using microwave irradiation, a mixture of hydrogen peroxide (H2 O2 ) and tartaric acid (TA) can initiate decomposition of the epoxy matrix up to 95% yield, leaving behind CFs with 92% tensile strength and 94% strain-to-failure retentions compared to the original CFs. Less than 2 min microwave irradiation was used which makes this approach considerably promising for the fast reclamation of the carbon fibre composites. The repetition of reclamation for the second and third times, which have been performed on the composite laminates re-manufactured using the reclaimed CFs, indicated that further reductions in the CFs mechanical performance are typically less than 5% after first reclamation process. Our proposed reclamation process changed surface properties of the reclaimed CFs compared to original CFs, which led to a significant increase in interfacial performance of the recycled CFs-epoxy composites. Moreover, the re-manufactured composite laminates using the reclaimed CFs showed highly comparable flexural strength and modulus, compared to its original composite laminates. Graphical abstract: Image 1